Extended cardiac ambulatory rhythm monitoring in adults with congenital heart disease: Arrhythmia detection and impact of extended monitoring. (3rd January 2019) - Schultz, Karen E.; Lui, George K.; McElhinney, Doff B.; Long, Jin; Balasubramanian, Vidhya; Sakarovitch, Charlotte; Fernandes, Susan M.; Dubin, Anne M.; Rogers, Ian S.; Romfh, Anitra W.; Motonaga, Kara S.; Viswanathan, Mohan N.; et al.
Abstract: Background: Arrhythmias are a leading cause of death in adults with congenital heart disease (ACHD). While 24‐48‐hour monitors are often used to assess arrhythmia burden, extended continuous ambulatory rhythm monitors (ECAM) can record 2 weeks of data. The utility of this device and the arrhythmia burden identified beyond 48‐hour monitoring have not been evaluated in the ACHD population. Additionally, the impact of ECAM has not been studied to determine management recommendations. Objective: To address the preliminary question, we hypothesized that clinically significant arrhythmias would be detected on ECAM beyond 48 hours and this would lead to clinical management changes. Methods: A single center retrospective cohort study of ACHD patients undergoing ECAM from June 2013 to May 2016 was performed. The number and type of arrhythmias detected within and beyond the first 48 hours of monitoring were compared using Kaplan‐Meier curves and Cox proportional hazard models. Results: Three hundred fourteen patients had monitors performed [median age 31 (IQR 25‐41) years, 61% female). Significant arrhythmias were identified in 156 patients (50%), of which 46% were noted within 48 hours. A management change based on an arrhythmia was made in 49 patients (16%). Conclusions: ECAM detects more clinically significant arrhythmias than standard 48‐hour monitoring in ACHD patients. Management changes, including medication changes, further testing or imaging, and procedures, were made based on results of ECAM. Recommendations and guidelines have been made based on arrhythmias on 48‐hour monitoring; the predictive ability and clinical consequence of arrhythmias found on ECAM are not yet known.